Descriptive Study of Learning Interest of Grade VIII Students of SMP Muhammadiyah 2 Tarakan City - Devi Ayu Safitri; Siti Rahmi; Zainal Abidin Muhja (Journal of Social Science and Economics (JOSSE), 2025)
This study aims to analyse the learning interests of grade VIII students at SMP Muhammadiyah 2 Tarakan City and the factors that affect them. This study uses a descriptive qualitative approach with the main informants, namely grade VIII students, subject teachers, and homeroom teachers. Data sources were obtained from direct observations, in-depth interviews, and documentation of learning activities. The data analysis technique uses the Miles and Huberman interactive model, namely data reduction, data presentation, and conclusion drawn. The results showed that students' learning interests were in the medium category, influenced by internal factors such as motivation, perception of the material, and curiosity; as well as external factors such as teachers' teaching methods, the role of parents, and learning environment conditions. Teachers who can create an interactive and fun learning atmosphere are proven to increase students' interest in learning. Family support is also a significant factor in encouraging students' active involvement in the learning process.